2009
DOI: 10.1101/gr.094482.109
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation tag sequencing for cancer gene expression profiling

Abstract: We describe a new method, Tag-seq, which employs ultra high-throughput sequencing of 21 base pair cDNA tags for sensitive and cost-effective gene expression profiling. We compared Tag-seq data to LongSAGE data and observed improved representation of several classes of rare transcripts, including transcription factors, antisense transcripts, and intronic sequences, the latter possibly representing novel exons or genes. We observed increases in the diversity, abundance, and dynamic range of such rare transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
260
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(267 citation statements)
references
References 44 publications
6
260
0
1
Order By: Relevance
“…These 17 nt 'tags' are sequenced in a high-throughput manner and the number of occurrences of each unique tag is counted, resulting in digital gene expression profiles where tag counts reflect expression levels of the corresponding transcript. 34 A total of 20 288 unique gene transcripts with a tag count greater than 1 were identified. The transcripts showing a median count equal to zero across all samples were filtered out.…”
Section: Biomarker Identificationmentioning
confidence: 99%
“…These 17 nt 'tags' are sequenced in a high-throughput manner and the number of occurrences of each unique tag is counted, resulting in digital gene expression profiles where tag counts reflect expression levels of the corresponding transcript. 34 A total of 20 288 unique gene transcripts with a tag count greater than 1 were identified. The transcripts showing a median count equal to zero across all samples were filtered out.…”
Section: Biomarker Identificationmentioning
confidence: 99%
“…We used digital gene expression (Morrissy et al 2009) to identify genes that are misregulated in sd E3 mutants and genes showing evidence of allelic imbalance in SAM/ORE "hybrids." This approach is similar to RNA-seq, but the cDNA is treated with a restriction enzyme (NlaIII) during library preparation, causing all sequence reads to begin at a restriction site.…”
Section: Digital Gene Expressionmentioning
confidence: 99%
“…The tag number of each contig was counted and normalized by the TPM algorithm (Morrissy et al, 2009). Results showed that the cloned IbPP2A1 was ubiquitously expressed in all of the seven tissues, although expression levels varied (Figure 4).…”
Section: Spatial Expression Patterns Analysesmentioning
confidence: 99%
“…The number of mapped tags were counted, and TPM values (transcripts per million clean tags) (Morrissy et al, 2009) were calculated and used for the quantification of each transcript in the different sweet potato samples.…”
Section: Expression Pattern Analyses Based On Dge Profilingmentioning
confidence: 99%